[Text not reproducible in ascii]: Etymological and sociocultural observations on the concepts of disease and divine (dis)favour in ancient Greece - Willi, A (2008)
After a brief discussion of earlier etymological theories, this article proposes a new analysis of the Greek noun 'disease' as a possessive compound *n-osw-os 'not having *(hi)osu', the second constituent of which is cognate with Hitt. āssu 'well-being'; just like the latter, Greek are characteristically sent or removed by divinities. Moreover, the reconstruction of an abstract noun *(hi)osu 'well-being (resulting from divine favour)' can serve as the etymological basis for the somewhat obscure Greek notion of which refers to the state of something that is endowed with such *(hi)osu; in fact, phraseological parallelisms between texts from various parts of the Greek world as well as ancient Anatolia point to a common conceptual framework behind all these words.